Evaluating lanreotide as maintenance therapy after first-line treatment in patients with non-resectable duodeno-pancreatic neuroendocrine tumours. Issue 5 (May 2017) - Lepage, Côme; Dahan, Laetitia; Bouarioua, Nadia; Toumpanakis, Christos; Legoux, Jean-Louis; Le Malicot, Karine; Guimbaud, Rosine; Smith, Denis; Tougeron, David; Lievre, Astrid; Cadiot, Guillaume; Di Fiore, Frédéric; et al.
Abstract: Introduction: Patients with metastatic or locally advanced, non-resectable, grade 1 or 2 well-differentiated duodeno-pancreatic (WDDP) NETs are treated following European guidelines. Patients (Pts) with aggressive disease, i.e. progressive and/or symptomatic metastases and/or with significant hepatic invasion (>30–50%), and/or bone metastases, anti-tumour therapy should receive systemic combination of chemotherapy once disease control is obtained. Aim(s): The aim is to stop chemotherapy until progression. REMINET is an academic randomized, double-blind, placebo-controlled, phase II/III study designed to evaluate lanreotide (LAN) as maintenance treatment after L1 chemotherapy in G1-G2 WDDP NET. Materials and methods: Main eligibility criteria: adults pts with a metastatic (synchronous or metachronous) or locally advanced, non-resectable, grade 1 or 2 WDDP NETs and documented control disease after L1 therapy at least 4 weeks prior to randomization. Results: 222 patients will be randomly assigned in a 1:1 ratio to receive 120 mg LAN or placebo, every 28 days, until disease progression or unacceptable toxicity. The aim of the phase II part is to demonstrate a 6-months PFS >45% in LAN arm. Secondary endpoints are PFS according to central review, overall survival, safety and quality of life. A bio-bank of frozen blood will be constituted. Conclusion: The study is currently open in France, Germany, Belgium, United Kingdom and Ireland. A total of 25 patients are randomized (NCT02288377).